Impact of Ecodriving on fuel emissions and consumption on road of Quito - Leguísamo Milla, Julio César; Llanes Cedeño, Edilberto; Rocha Hoyos, Juan (Enfoque UTE, 2020)
This article presents the results of the impact of ecodriving on fuel consumption and the emission factors of polluting gases from a gasoline vehicle when performing road testing in the city of Quito, located at 2 810 meters above sea level. A route with traffic validated by the Technology Transfer Center has been selected for the training and investigation of vehicle emission control. A Chevrolet Aveo Family was used as a test vehicle, , considering is the bestselling vehicle in the city at the moment. And the equipment used to measure fuel consumption and the concentration of emissions was an onboard gas analyzer and a canister. The success and the measuring of the data in this experimentation were determined using the STATGRAPHICS Centurion XVI software. The results showed significant differences in fuel consumption and pollutant emissions of CO and NOx when applying an efficient driving, except for the HC in which there is no significant difference, but the emission is lower when is used on standard driving.